If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 114 + -2x = 5x + 9 Reorder the terms: 114 + -2x = 9 + 5x Solving 114 + -2x = 9 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 114 + -2x + -5x = 9 + 5x + -5x Combine like terms: -2x + -5x = -7x 114 + -7x = 9 + 5x + -5x Combine like terms: 5x + -5x = 0 114 + -7x = 9 + 0 114 + -7x = 9 Add '-114' to each side of the equation. 114 + -114 + -7x = 9 + -114 Combine like terms: 114 + -114 = 0 0 + -7x = 9 + -114 -7x = 9 + -114 Combine like terms: 9 + -114 = -105 -7x = -105 Divide each side by '-7'. x = 15 Simplifying x = 15
| 2*0=-y+2 | | 13x+8-4x+1= | | 6x+12=120-6x | | 7x-2=2x+13 | | x+x+y=100 | | 7x-13=50 | | 5x-5=13x-69 | | 5x+36=12x-27 | | 14x+8y=74 | | (x-1)9=6x+18 | | -7+-2= | | y^2+3y=1 | | 23x-12y=44 | | r^5=96 | | 108-3(8x-5)=51 | | 2x^50=0 | | 3(3+x)=2x+10 | | -9+6= | | y=-0.8*55+102 | | y=-0.8*45+102 | | y=-0.8*35+102 | | y=-0.8*25+102 | | -(3y+3)-(-2y-5)=-5 | | -2(t+3)-t-4=-3(t+4)+2 | | 9(2x-3)=9 | | 7*3+3y=84 | | 7x+3(0)=84 | | x+1.2=(-4.6) | | 8(3x-3)=2(12x+1) | | 7(0)+3y=84 | | -9(t-2)-(t+7)=3 | | 8x-45=6x-5 |